Analisis Faktor – Faktor yang Mempengaruhi Produksi Getah Pinus di Kabupaten Poso - Jesi A. Lateka; Tohap Manurung; Jantje D. Prang (d\'Cartesian: Jurnal Matematika dan Aplikasi, 2019)
JESI APRIANI LATEKA. Analysis of Factors Affecting Pine Gum Production in Poso District. Supervised by JANTJE D. PRANG as main supervisor and TOHAP MANURUNG as a co-supervisor.            Poso Regency is a center of productivity for pine resin in Central Sulawesi, so it is very important to know the factors that influence the production of pine sap in Poso District. Referring to several previous studies, the accumulation of various factors can cause a problem or an event triggered by various previous events, to predict the use of multiple linear regression equations that can summarize these various factors. The data used in this study are data on the land area of each group (X1 ), the number of group workers (X2) and the number of hours of group work (X3). Based on the results of multiple linear regression analysis there is a symptom of multicollinearity between the variables of the number of workers and the number of hours worked, therefore to overcome this one variable is taken, namely the number of workers. The results of the analysis show that the variable area of land and the number of labor simultaneously affect the production of pine sap with a determination coefficient of 93%. Kata kunci:   Analysis of Multiple Linear Regression, Pine Forest in Poso District